Classical solution of the cauchy problem for Biwave equation: application of fourier transform - Korzyuk, Victor; Vinh, Nguyen Van; Minh, Nguyen Tuan (Mathematical Modelling and Analysis, 2012)
In this paper, we use some Fourier analysis techniques to find an exact solution to the Cauchy problem for the n-dimensional biwave equation in the upper half-space ℝ n × [0, +∞).